Relationship Between Lumbar Muscle Strength and Proprioception After Fatigue in Men with Chronic Low Back Pain - Bilge Yılmaz,; Evren Yaşar,; Mehmet Ali Taşkaynatan,; Ahmet Salim Göktepe,; İlknur Tuğcu,; Kamil Yazıcıoğlu,; Haydar Möhür, (Archives of Rheumatology, 2010)
Objective: To evaluate the relationship between lumbar position sense and trunk muscle strength, to investigate the effect of fatigue on this relationship, and the effect of fatigue on proprioception in patients with chronic low back pain (CLBP). Materials and Methods: A cross-sectional study was conducted to determine lumbar position sense and trunk muscle strength in 19 males with low back pain and in 20 healthy controls. After neurological examination every subject was evaluated for repositioning error (RE) with Cybex Norm isokinetic dynamometer using the trunk extension-flexion modular component. Then, every subject underwent a concentric/concentric exercise program including extension and flexion exercises performed actively for 15 times with the velocity of 60° / second. Finally, the RE test was repeated. Results: Differences in RE between the groups were significant before and after fatiguing exercise procedure. After fatigue, changes in RE were found significant in both groups. Differences in flexion peak torque and total work between the groups were significant. Second RE measurement was found to be correlated with flexion peak torque and total work in control group. Conclusion: The results of this study reveals that flexor muscle strength is significantly lower in patients with CLBP. RE was significantly higher in patients compared to the healthy controls. We found that abdominal muscle strength was moderately correlated with position sense in healthy population after fatigue, whereas there was no correlation in patient group. (Turk J Rheumatol 2010; 25: 68-71)